A RaDiCAL gene hunt. Issue 3 (June 2017) - Pupavac, Mihaela; Zawati, Ma'n H.; Rosenblatt, David S.
الملخص: في السنوات العديدة الماضية، شرعت الاتحادات للأمراض النادرة في استهداف اكتشاف الجينات المسببة للأمراض في الأمراض المندلية، باستخدام أساليب تسلسل الجيل القادم. وعلى الرغم من نجاح هذه المبادرات الواسعة التطبيق، لم يتعرف الباحثون على المسببات الجينية للكثير من الأمراض. يدرس "التعاون للأمراض النادرة لمواضع الصبغيات الجسدية" (راديكال) أندر الأمراض، التي قد لا يتوفر بها سوى مستلفت واحد، في سبيل التعرف على الجينات المفترَضة المسببة للأمراض. تستعرض هذه المقالة الكيفية التي تعامل بها التعاون للأمراض النادرة لمواضع الصبغيات الجسدية مع بعض التحديات لاستحداث وثائق الموافقة المسبقة المطلوبة للمشاركين الدوليين. كما أنها تأخذ في الاعتبار، الموضوع الناشئ "حق ألا يعلم" في تصميم الدراسة. Abstract: In the past several years, rare disease consortia have embarked on the discovery of disease-causing genes for Mendelian diseases using next generation sequencing approaches. Despite the success of these large-scale initiatives, many diseases still have no identified genetic cause. The Rare Disease Collaboration for Autosomal Loci (RaDiCAL) studies the rarest diseases, where occasionally only a single proband is available to identify putative disease-causing genes. This article reviews how "RaDiCAL" addressed some of the challenges in generating informed consent documents for international participants and considers the emerging topic of the "right not to know" in study design.